Sexual harassement in employment : recent judicial and arbitral trends. - AEBERHARD-HODGES, Jane (1996)
Describescurrent trends against sexual harrassment in employment, drawing on a wide literature. Points out the use of labour and other legislation on equal employment opportunities, human rights, helth and sfety, and tort and criminal law for countering sexual harassment. Looks at the questions of liability, remedies and sanctions.